„Schwierige Lieder“ – volkssprachlich, binär, zweistimmig: Gustav Jacobsthals Arbeit an der „Mondsee-Wiener“ Liederhandschrift des Mönchs von Salzburg (A-Wn, Cod. 2856). Eine Hinführung - Sühring, Peter (Die Musikforschung, 2025)
The article provides an insight into the already known but not yet well documented work of Gustav Jacobsthal in Strasbourg in the second half of the 1870s, when he prepared the edition and commentary on the Mondsee-Wiener-Lieder manuscript (A-Wn, Cod. 2856), but which he could not complete. Te complicated genesis of this research and editorial project, for which he had joined forces with his friend, the Germanist Wilhelm Scherer, and its ultimate failure are described. Furthermore, the interpretative approaches are explained which Jacobsthal had already achieved in terms of content, in addition to his annotated complete copy of the codex, and supported with quotations from the diplomatic transcription of Jacobsthal’s notes. Jacobsthal’s research methods and his preliminary results concern questions of the numbering of the songs and the scribal hands, the rationale for emendations, the measurement of the beat and the relationship between the metre of the language and musical rhythm. Jacobsthal’s views are compared and contrasted with other attempts at editing and interpretation, undertaken at the same time and shortly thereafter by other researchers, and are selectively compared with perspectives on the current state of research.